2015
DOI: 10.1002/mbo3.288
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mycobacterium smegmatis sigF mutant and its regulon: overexpression of SigF antagonist (MSMEG_1803) in M. smegmatis mimics sigF mutant phenotype, loss of pigmentation, and sensitivity to oxidative stress

Abstract: In Mycobacterium smegmatis, sigF is widely expressed during different growth stages and plays role in adaptation to stationary phase and oxidative stress. Using a sigF deletion mutant of M. smegmatis mc2155, we demonstrate that SigF is not essential for growth of bacterium. Deletion of sigF results in loss of carotenoid pigmentation which rendered increased susceptibility to H2O2 induced oxidative stress in M. smegmatis. SigF modulates the cell surface architecture and lipid biosynthesis extending the repertoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 39 publications
2
52
0
Order By: Relevance
“…Interestingly, a large portion (29 genes, 78.4%) of 37 repressed genes overlaps the known SigF regulon of M. smegmatis (Fig. and Supporting Information Table S2) (Singh et al ., ). The significantly repressed genes other than the SigF regulon and the genes of unknown function include aceA ( MSMEG_0911 ) encoding isocitrate lyase (McKinney et al ., ; Munoz‐Elias and McKinney, ), as well as glpK ( MSMEG_6759 ) and glpD ( MSMEG_6761 ) encoding glycerol kinase and glycerol‐3‐phosphate dehydrogenase, respectively (Seno and Chater, ; Titgemeyer et al ., ), implying downregulation of the glyoxylate shunt and glycerol metabolism in the Δ f1f2f3 mutant.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Interestingly, a large portion (29 genes, 78.4%) of 37 repressed genes overlaps the known SigF regulon of M. smegmatis (Fig. and Supporting Information Table S2) (Singh et al ., ). The significantly repressed genes other than the SigF regulon and the genes of unknown function include aceA ( MSMEG_0911 ) encoding isocitrate lyase (McKinney et al ., ; Munoz‐Elias and McKinney, ), as well as glpK ( MSMEG_6759 ) and glpD ( MSMEG_6761 ) encoding glycerol kinase and glycerol‐3‐phosphate dehydrogenase, respectively (Seno and Chater, ; Titgemeyer et al ., ), implying downregulation of the glyoxylate shunt and glycerol metabolism in the Δ f1f2f3 mutant.…”
Section: Resultsmentioning
confidence: 97%
“…SigF is known to be involved in cell surface stress (heat, SDS, antibiotics, etc.) and oxidative stress responses, as well as the adaptation to stationary growth phase (Provvedi et al ., ; Humpel et al ., ; Singh et al ., ). This finding implies that the genes of the SigF regulon are positively regulated by FurA in an indirect way.…”
Section: Discussionmentioning
confidence: 97%
“…14 β-sheets (numbered [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Similarly, Usfx secondary structure is characterized by 3 α-helices (numbered i-iii) and 5 β-sheets (numbered i-v) (Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…SigF is another sigma factor, which is considered a stress response factor as its expression increases in MTB under stress conditions, such as nutrient starvation, cold shock, and antibiotics . In another study, cell wall–associated proteins were found differentially regulated after over expression of SigF in MTB . The activity of sigma factors is controlled by sigma factor antagonists called anti‐sigma factors, which bind with sigma factors and prevent their interaction with RNAP and thus, preventing expression of genes controlled by that specific sigma factor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation